Entre a segurança nacional e os direitos fundamentais : reformulação conceitual do crime político e a defesa das instituições democráticas - Wunderlich, Alexandre Lima (2016)
This research discusses the implementation of the Authoritarian Model of National Security in Brazil – with fascist inspiration, and recourse to political crime as a way of sustaining power, mistaking it for a common crime and causing a number of acts of State violence – even the adoption of the Model of Protection and Defense of the State of Law and its Democratic Institutions provided for in the 1988 Federal Constitution. The research investigates the construction of the concept of political crime based on the National Security Doctrine and, in view of the vacuum of its meaning and interest in the protection of internal security of the State of Law – proposes its legal and doctrinal redefinition. The thesis establishes vectors to face the problem of the contingency of the current Brazilian social, political and cultural stages, starting from the required reaffirmation of the defense of the State of Law and operation of its Republican Institutions as a basis for the implementation of fundamental rights. Without ignoring the connections and impact on internal and external dimensions in the context of legal action and state policy, it chooses to focus on the issue in the internal sphere, primarily confined to the defense of democratic institutions.